2021
DOI: 10.48550/arxiv.2104.03030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-(ir)reversibility in active matter: from micro to macro

Abstract: Active matter encompasses systems whose individual consituents dissipate energy to exert propelling forces on their environment. This rapidly developing field harbors a dynamical phenomenology with no counterpart in passive systems. The extent to which this is rooted in the breaking of time-reversibility has recently triggered an important theoretical and experimental activity which is the focus of this review. Building on recent progress in the field, we disentangle the respective roles of the arrow of time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 157 publications
(255 reference statements)
0
4
0
Order By: Relevance
“…As an example, this method has been employed to show the nonequilibrium nature of red blood cells [68]. Several other methods, based, e.g., on the detection of probability currents in the phase space or the breakdown of time-reversal symmetry, have also been developed [36,42,64,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85].…”
mentioning
confidence: 99%
“…As an example, this method has been employed to show the nonequilibrium nature of red blood cells [68]. Several other methods, based, e.g., on the detection of probability currents in the phase space or the breakdown of time-reversal symmetry, have also been developed [36,42,64,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85].…”
mentioning
confidence: 99%
“…However, assessing the success of effective temperature ideas to describe nonequilibrium steady states remains largely empirical. Recent work by O'Bryne and Tailleur demonstrated that the dynamics of tactic active matter can be rigorously mapped to effective passive systems at a hydrodynamic level [34,35]. On a microscopic level, active forces under certain limits can act as traditional thermal forces by satisfying an effective fluctuation-dissipation theorem (FDT) [36,37].…”
mentioning
confidence: 99%
“…Time reversal symmetry breaking (TRSB) in active matter systems arises from the self-propelled motion of individual particles, driven by the continuous injection of energy into the system [1,2]. TRSB is linked to the emergence of steady-state currents in phase-space, a clear signature of a system's departure from equilibrium, which can be quantified in terms of the global rate of entropy production [3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%